2017
DOI: 10.1103/physrevb.95.224421
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocrystalline anisotropy of La- and Co-substituted M -type strontium ferrites: Role of Co2+ and Fe<

Abstract: We have systematically investigated magnetic properties of La and Co substituted SrFe12O19 using single crystals. By utilizing travelling solvent floating zone technique, we have grown single crystals over wide range of substitution content, and examined their saturation moments and magnetocrystalline anisotropy. With increasing content of La and Co, saturation moment at 300 K monotonically increases. The increment of magnetocrystalline anisotropy is almost proportional to the content of Co. In addition, furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…It has been reported that the magneto-crystalline anisotropy and coercive field of M-type strontium hexaferrite can be increased or reduced according to the concentrations of the substituted La 3+ cations. [20][21][22][23] Fe or Sr lattice sites are argued to be the strong preference for the La 3+ substitutions, which are thought to be responsible for the intrinsic physical mechanism of mag-netism modulation. Many efforts using the abovementioned techniques have been devoted to confirming the site preference of the substituted ions in M-type strontium hexaferrite.…”
Section: mentioning
confidence: 99%
“…It has been reported that the magneto-crystalline anisotropy and coercive field of M-type strontium hexaferrite can be increased or reduced according to the concentrations of the substituted La 3+ cations. [20][21][22][23] Fe or Sr lattice sites are argued to be the strong preference for the La 3+ substitutions, which are thought to be responsible for the intrinsic physical mechanism of mag-netism modulation. Many efforts using the abovementioned techniques have been devoted to confirming the site preference of the substituted ions in M-type strontium hexaferrite.…”
Section: mentioning
confidence: 99%
“…Still, important properties such as the electronic gap have not yet been determined. In the last 2 decades, significant effort has been devoted to improve its magnetic performance, particularly for permanent magnet applications, by chemical substitution and nanostructuring [3][4][5][6][7] . Nanometric thin SFO platelets have been recently characterized combining fundamental experimental techniques, as X-ray absortion based and Mössbauer spectroscopies, to density functional theory (DFT) calculations intended to rationalize Oxygen K absortion edge spectrum measurements 8 .…”
mentioning
confidence: 99%
“…The internal crystal structure of M‐type ferrite can be changed by ion substitution, which makes the lattice constant, magnetocrystalline anisotropy and total magnetic moment change. The ion substitution of M‐type ferrite mainly includes three aspects: (1) the ion substitution for Me 2+ ions, [7–13] (2) the ion substitution for Fe 3+ ions, [14–21] and (3) the joint substitution of ions [22–33] . Roy et al [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The ion substitution of M-type ferrite mainly includes three aspects: (1) the ion substitution for Me 2 + ions, [7][8][9][10][11][12][13] (2) the ion substitution for Fe 3 + ions, [14][15][16][17][18][19][20][21] and (3) the joint substitution of ions. [22][23][24][25][26][27][28][29][30][31][32][33] Roy et al [10] synthesized LaÀ Sm substituted strontium ferrites SrAl 4 (La 0.5 Sm 0.5 ) x Fe 8-x O 19 (0 � x � 1.5) by spontaneous combustion method, and found that with the increase of LaÀ Sm substitution amount, B r increased, while H cj decreased and when x = 1.0, the optimized properties were B r = 5.19 kg, H cj = 6.18 kOe, (BH) max = 6.69 MGOe and T c = 492 K. Trusov et al [22] studied the strontium hexagonal ferrite prepared by using the citrate melt autoignition method, and found that the H c reach the giant value of 21.3 kOe at M s of 14 emu/g, this effect is due to the increase of magnetocrystalline anisotropy caused by the distortion of crystal structure. Mishra et al [25] studied the magnetic properties of M-type ferrites SrFe 12-x Cu x O 19 and Sr 1-x La x Fe 12-x Cu x O 19 , and found that the presence of La 3 + increased the values of M s and H c , but the lattice distortion caused by La 3 + substitution reduced the value of T c , the enhancement of the hyperfine field value of 12k crystal site by La 3 + -Cu 2 + co-substitution made M s higher than that of SrM replaced by Cu 2 + .…”
Section: Introductionmentioning
confidence: 99%